Pengaruh Komposisi Gypsum Terhadap Setting Time Pada Proses Produksi Semen PCC - Mala Hayati Nasution; Nevybryanti Bunga Nurcahyo Putri; Lukmilayani Candra (CHEMICA: Jurnal Teknik Kimia, 2019)
Cement is a national strategic commodity. Based on data from the Ministry of Industry of the Republic of Indonesia in 2017, the total installed capacity of the national cement industry is 92.7 million tons per year with a consumption rate of 65 million tons per year. The raw materials for the cement production process are limestone, iron sand, clay, silica sand, and gypsum. A comparison of the composition of each raw material influences the type and characteristics of the cement produced. Gypsum is a raw material that affects the quality of the final cement product. Gypsum acts to regulate the hardening time and inhibits the binding time so that it can be used for a long time. This research was conducted to study the effect of gypsum composition on setting time in the Portland Composite Cement (PCC) production process. Gypsum was Tanjung Jati gypsum. Variation of gypsum composition were 0-5% -weight. Â Based on SNI 15-2049-2004, the minimum initial setting time is 45 minutes and the maximum final setting time is 375 minutes. Based on the results of the research, PCC cement with 0 - 5%--weight gypsum met these standards. Increased gypsum composition causes an increase in both initial and final setting time.